Evaluation of a modified proportional margin approach for complete surgical excision of canine cutaneous mast cell tumours and its association with clinical outcome. (23rd July 2020) - Saunders, Harvey; Thomson, Maurine J.; O'Connell, Kathleen; Bridges, Janis P.; Chau, Lincoln
Abstract: Canine cutaneous mast cell tumours (MCTs) represent a common neoplasm in veterinary practice. Several reported techniques are available to guide surgical excision. Our study examined one hundred cutaneous MCTs that were excised surgically using a modified proportional margin approach. A 2 cm lateral margin upper limit was applied for any tumour diameter that exceeded this size with a deep surgical margin of one fascial plane applied. A retrospective, cross‐sectional study with follow‐up was used to determine the clinical utility of this excision technique. Associations between explanatory variables of tumour size and grade were compared with outcomes of complete excision and size of histologic tumour‐free margins (HTFM) using the appropriate Pearson's χ 2 and Fisher's exact tests. Follow‐up data evaluated tumour recurrence and patient survival. Ninety‐five percent of MCTs (95/100) were completely excised. No significant association in the achievement of complete excision between low‐ and high‐grade MCTs ( P = .48) was noted. Tumour size was not associated with the rate of complete excision ( P = .06). Tumour grade and size did not influence the size of the HTFM ( P = .94 and P = .14, respectively). Overall, a recurrence rate of 3% (3/100 tumours) and de novo MCT development rate of 7.7% (5/65 dogs) was noted, with median follow‐up period of 593 days (range 180‐1460 days). Post‐operative metastases were seen in 4.6% of dogs (3/65). Therefore, a modified proportional margin approach with 2 cm lateral margin upper limit is a suitable technique to guide surgical excision of canine cutaneous MCTs.